2020
DOI: 10.3389/fnbeh.2020.00099
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Choice Biases in Mice and Humans

Abstract: The contribution of non-sensory information processing to perceptual decision making is not fully understood. Choice biases have been described for mice and humans and are highly prevalent even if they decrease rewarding outcomes. Choice biases are usually reduced by discriminability because stimulus strength directly enables the adjustments in the decision strategies used by decision-makers. However, choice biases could also derive from functional asymmetries in sensory processing, decision making, or both. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…At the extreme, high levels of choice stereotypy characterize some human psychopathologies and mental disorders [ 10 ]. Similar manifestations of sub-optimal choice behavior have also been documented for rats [ 11 ], mice [ 6 , 12 , 13 ], and pigeons [ 14 ].…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…At the extreme, high levels of choice stereotypy characterize some human psychopathologies and mental disorders [ 10 ]. Similar manifestations of sub-optimal choice behavior have also been documented for rats [ 11 ], mice [ 6 , 12 , 13 ], and pigeons [ 14 ].…”
Section: Introductionsupporting
confidence: 60%
“…We thus hypothesized that if human participants stably exhibit side-choice biases, they should co-vary with other behavioral metrics when the same individuals solved unrelated tasks. Employing forced and unforced tasks [ 13 ], we confirmed that participants exhibited different but consistent proportions of side-choice biases ( i . e ., decisional biases) across experimental days.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations